Paintings to my ears: A method of studying subjectivity in audio description for art museums - Luque, M Olalla; Soler Gallego, Silvia (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2019)
An increasing number of museums are using audio description (AD) to provide access for visually impaired visitors to their collections by means of a wide range of mobile devices and apps. However, research in this field is still limited. The present article proposes a methodological approach that combines interviews and corpus analysis for studying audio-descriptive guides of art museums. More specifically, the proposed methodology focuses on the study of subjectivity, which has become a controversial aspect of AD in the past few years and the focus of a number of studies. The article offers a step-by-step description of the methodology and illustrates it with data from a study carried out by the authors on this type of multimodal communication.